A Phase II Trial of Capecitabine Concomitantly With Whole‐Brain Radiotherapy Followed by Capecitabine and Sunitinib for Brain Metastases From Breast Cancer. (6th November 2014) - Niravath, Polly; Tham, Yee Lu; Wang, Tao; Rodriguez, Angel; Foreman, Claudette; Hilsenbeck, Susan G.; Elledge, Richard; Rimawi, Mothaffar
Abstract : Background: Brain metastasis from breast cancer presents a significant threat to women's health and quality of life. Capecitabine and sunitinib have shown some activity in this setting; therefore, we conducted a single‐arm phase II trial with these agents. Methods: Patients with breast cancer and central nervous system (CNS) metastases received whole‐brain radiotherapy concurrently with capecitabine (1, 000 mg/m 2 per day for 14 consecutive days), followed by concomitant capecitabine (2, 000 mg/m 2 per day for 2 weeks followed by a 1‐week break) and sunitinib (37.5 mg daily, continuously). The primary endpoint was progression‐free survival (PFS). Results: Of 25 planned patients that would be required to detect a 4‐month improvement (from 5 to 9 months) in median PFS with 80% power, 12 were enrolled, and the study was then closed for slow accrual. Median PFS was 4.7 months, and median overall survival was 10 months. In the CNS, 25% had progressive disease, and 83% experienced extra‐CNS progression. The most common side effects were fatigue and nausea. Conclusion: In 12 evaluable patients studied, concurrent capecitabine and whole‐brain radiation followed by capecitabine and sunitinib did not extend PFS over historical rates and was associated with significant toxicity. Our study was small and closed due to slow accrual. Abstract : 摘要 背景 . 乳腺癌脑转移极大地威胁着女性的健康和生活质量。卡培他滨和舒尼替尼在这类患者中已显示出一些活性，我们使用这些药物开展了一项单臂 II 期试验。 方法 . 本研究中的乳腺癌中枢神经系统（CNS）转移患者接受了全脑放疗联合卡培他滨（每日1 000 mg/m 2 ，连续14天）同步化疗，继以卡培他滨（每日2 000 mg/m 2 ，连续 2 周后间歇 1 周）联合舒尼替尼（每日 37.5 mg，连续给药）治疗。主要终点为无进展生存（PFS）。 结果 . 为获得 80% 的把握度以检测到中位 PFS 获得 4 个月的改善（从 5 个月延长至 9 个月），研究计划招募 25 例患者，但在入组 12 例之后因受试者例数增长缓慢而停止招募。中位 PFS 为 4.7 个月，中位总生存（OS）为 10 个月。 CNS 方面，25% 的患者疾病进展，83% 发生 CNS 外进展。最常见的不良事件为疲乏和恶心。 结论 . 在 12 例可评价患者中，与历史记录相比，卡培他滨联合同步全脑放疗继以卡培他滨和舒尼替尼治疗未能延长 PFS ，并且与明显的毒性相关。本研究规模较小，且因入组缓慢而停止招募患者。 The Oncologist 2015;20:13